2017
DOI: 10.1044/2017_jslhr-s-17-0075
|View full text |Cite
|
Sign up to set email alerts
|

Sentence-Level Movements in Parkinson's Disease: Loud, Clear, and Slow Speech

Abstract: Sentence-level measures of articulatory movements are sensitive to both disease-related changes in PD and speaking-style manipulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 53 publications
6
35
2
Order By: Relevance
“…This discovery is consistent with Kearney's research [21] and can be well explained by Goozée's perspective [46], [55]. Kearney et al examined the association between the speech intelligibility and the articulatory movements of Parkinson's disease (PD) patients on sentence level [21] as impaired articulation is more likely to occur in connected speech in PD than at the syllable level [17], [18]. They found that compared to the normal pronunciation, PD appears larger movement sizes for loud, clear and slow speech, and faster speeds for loud, clear speech.…”
Section: B Articulation Velocity and Space Distributionsupporting
confidence: 92%
See 4 more Smart Citations
“…This discovery is consistent with Kearney's research [21] and can be well explained by Goozée's perspective [46], [55]. Kearney et al examined the association between the speech intelligibility and the articulatory movements of Parkinson's disease (PD) patients on sentence level [21] as impaired articulation is more likely to occur in connected speech in PD than at the syllable level [17], [18]. They found that compared to the normal pronunciation, PD appears larger movement sizes for loud, clear and slow speech, and faster speeds for loud, clear speech.…”
Section: B Articulation Velocity and Space Distributionsupporting
confidence: 92%
“…From the graph, we discovered that for words/sentences, patients actually pronounce faster than normal people by about 5mm/s, at 85mm/s. This discovery is consistent with Kearney's research [21] and can be well explained by Goozée's perspective [46], [55]. Kearney et al examined the association between the speech intelligibility and the articulatory movements of Parkinson's disease (PD) patients on sentence level [21] as impaired articulation is more likely to occur in connected speech in PD than at the syllable level [17], [18].…”
Section: B Articulation Velocity and Space Distributionsupporting
confidence: 78%
See 3 more Smart Citations